Subtypes of NanS-p sialate O-acetylesterase encoded by Stx2a bacteriophages - Pascal, Stefanía Belén (2020)
Shiga toxin (Stx)-producing Escherichia coli strains are foodborne pathogens that cancause severe human diseases, such as haemorrhagic colitis and haemolytic-uraemic syndrome. Stxsare encoded by bacteriophages (Stx phages) which show remarkable variations in genomecomposition and harbour several genes of unknown function. Recently, a gene encoding a sialateO-acetylesterase (NanS-p) was identified in some relevant Stx2a phages and it was suggested that itcould provide advantages for bacterial growth in the gut. The aim of this study was to analyse thepresence and sequence of nanS-p genes in available Stx2a phage genomes. A total of 59 DNAsequences of Stx2a phages were extracted from the NCBI GenBank database with the BLASTprogram using the stx2a sequence from phage 933W as query sequence, either as complete phagegenomes (45) or from bacterial genomes by subsequent analysis with PHASTER web server (14).Comparative analysis revealed that nanS-p was located downsteam stx2a in all genomes. Twentydifferent amino acid sequences of NanS-p were identified. Specifically, catalytic esterase domainsshowed only 11 possible sequences, with differences mainly observed in nine amino acid positions.Sequences corresponding to the N-terminal domain (DUF1737) showed three possible sequences,two of them closely related, while C-terminal domain was highly variable giving place to fourgroups with structural differences. Since sialate O-acetylesterase activity has been determined fromparticular Stx2a phages, new studies are necessary to evaluate if the NanS-p subtypes identified inthe present study also differ in their biological activity.